Effects of tank sloshing on submerged oil leakage from damaged tankers. (15th November 2018) - Lu, Jinshu; Yang, Zhenbo; Wu, Haoxiao; Wu, Wenfeng; Deng, Jiajia; Yan, Shiqiang
Abstract: In order to gain advanced understanding of the mechanism of the submerged oil leakage from damaged tankers subjected to wave-excited motions, a three-dimensional (3D) full scale numerical model is developed in this paper. The model is based on the three-phase Navier-Stokes equation and the continuity equation, which are solved by using the finite volume method (FVM). The volume of fluid (VOF) method is implemented to identify the interfaces between different phases and the k-ε turbulence model is employed to approximate the turbulence effects. The prototype of the oil tanker is taken as the side tank of VLCC, which is subjected to a periodically forced motions yielding a liquid sloshing inside the tank. After being validated by comparing its prediction with experimental data, the present model is utilized to a systematic investigation with wide range of applications including different motion amplitudes and periods. The dynamic characteristics of both the macroscopic parameters, e.g. the volume of the oil/water, and the microscopic parameters, e.g. the velocity distributions, are analyzed. The results fill the gap in the existing numerical and experimental work, in which the tank is assumed to be stationary, and produce a more reliable prediction on the dynamic process of the oil leakage and the stability of the damaged oil tankers subjected to wave actions. Highlights: A 3D full scale numerical model was developed to estimate dynamic characteristic of crude oil leakage from moving tank. The process of crude oil leakage was divided into three stages to explore mechanism of crude oil leakage. The mechanism model and characteristics of crude oil leakage from moving tank were presented. The flow field and free surface deformation were explored to validate mechanism of crude oil leakage.